2017
DOI: 10.1016/j.biomaterials.2017.01.018
|View full text |Cite
|
Sign up to set email alerts
|

miRNases: Novel peptide-oligonucleotide bioconjugates that silence miR-21 in lymphosarcoma cells

Abstract: Please cite this article as: Patutina OA, Bichenkova EV, Miroshnichenko SK, Mironova NL, Trivoluzzi LT, Burusco KK, Bryce RA, Vlassov VV, Zenkova MA, miRNases: Novel peptide-oligonucleotide bioconjugates that silence miR-21 in lymphosarcoma cells, Biomaterials (2017Biomaterials ( ), doi: 10.1016Biomaterials ( / j.biomaterials.2017 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
71
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(74 citation statements)
references
References 90 publications
3
71
0
Order By: Relevance
“…In fact, the binding affinity of the PNA incorporating guanidinium moiety toward single-stranded RNA (relevant to this study) was shown to be 14 times lower than that toward double-stranded RNA (Krishna et al, 2019). These results seemed to agree with our molecular modeling simulations, which demonstrated the possibility of hydrogen bonding interactions between the arginine sidechain with the N 7 and carbonyl O atoms of guanosine residues (Patutina et al, 2017). However, these interactions appeared to be ancillary, whereas the network of ionic interactions between arginine residues with backbone phosphate groups of RNA was shown to dominate such interactions.…”
Section: 'Single-label' Hybridizationsupporting
confidence: 87%
See 3 more Smart Citations
“…In fact, the binding affinity of the PNA incorporating guanidinium moiety toward single-stranded RNA (relevant to this study) was shown to be 14 times lower than that toward double-stranded RNA (Krishna et al, 2019). These results seemed to agree with our molecular modeling simulations, which demonstrated the possibility of hydrogen bonding interactions between the arginine sidechain with the N 7 and carbonyl O atoms of guanosine residues (Patutina et al, 2017). However, these interactions appeared to be ancillary, whereas the network of ionic interactions between arginine residues with backbone phosphate groups of RNA was shown to dominate such interactions.…”
Section: 'Single-label' Hybridizationsupporting
confidence: 87%
“…We have recently developed a new class of catalytic bioconjugates, as synthetic ribonucleases using amphipathic peptides, which only cleave RNA when conjugated to oligonucleotide recognition motifs (Mironova et al, 2002;Mironova, Boutorine et al, 2004;Mironova et al, 2006Mironova et al, , 2007Patutina et al, 2017Patutina et al, , 2019Pyshnyi et al, 1997;Staroseletz, Williams et al, 2017;Williams et al, 2015). These RNA-targeting synthetic nucleases are chemically-engineered by conjugation of short, catalytically-inactive peptides with oligonucleotide recognition motif components, which range from fully-through poorlyto non-complementary to the target RNA, in order to produce novel biologically-active molecules capable of recognizing and cleaving RNA sequences quantitatively.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although in modern life sciences gapmers [2,14,15] and siRNAs [16] are the preferred tools for achieving the site-specific cleavage of RNA strands, there is still interest in synthetic ribonucleases and recent years have seen important progress in the field. Effective catalysts that are based on metal ions [17][18][19][20][21][22][23], guanidines or polyamines [24][25][26][27], peptide conjugates [28][29][30][31][32], and deoxyribozymes [33,34] have been described. Starting from heterocyclic guanidine analogs [35], we have investigated the conjugates of tris(2-aminobenzimidazoles) and different types of oligonucleotides, such as DNA [36], PNA [37,38], or DNA-LNA mixmers [39], which were shown to act as sequence-specific metal-free RNA cleavers.…”
Section: Introductionmentioning
confidence: 99%